Viable Airborne and Deposited Microorganisms inside the Historical Museum of Crete - Eleftheria Katsivela; Louisa Raisi; Mihalis Lazaridis (Aerosol and Air Quality Research)
Abstract Measurements of the ambient viable microbe concentrations and of the microbial deposits on surfaces were performed in the Historical Museum of Crete over a period of two years. The levels of the airborne microbes in the museum rooms showed considerable variability, which was mainly related to the indoor activity (such as the number of visitors); indoor environmental conditions, including the air exchange rate; and exhibits’ chemical compositions and storage conditions as well as the conservation treatments and cleaning techniques to which they had been subjected. An enrichment of acid-producing bacteria, heterotrophic bacteria, and autotrophic chemolithotrophic bacteria was encountered indoors, but a considerable decrease in the viable microbes, ranging from 5.5% to 76%, was detected after the deployment of photocatalytic ionizers at the different measurement sites inside the museum. These ionizers mainly improved the air quality by reducing acid-producing bacteria, which potentially contribute to deterioration in cultural heritage objects. The microbial colonization on 24 different painting materials and surfaces collected into model artwork essays, which had not received any preservation treatment, was examined for an exposure period of 18 months. The bacterial depositions on the paintings gradually colonized, depending on the material and the surface, resulting in concentrations of 10–300,000 CFU cm−2. Although airborne fungi were observed in the exhibition rooms (at an average yearly concentration of 143 ± 115 CFU m−3), no fungal growth was detected on the majority of the painting materials in the model essays. Only the tempera, charcoal, wax pastel, and carton board displayed fungal colonization, which occurred very slowly and produced low concentrations of 70–200 CFU cm−2.